The Relationship of Age, Gender, and Socio-Economic Factors with Patients Anxiety Levels (A Review of Early Adult Patients at the Gusti Hasan Aman Oral and Dental Hospital, Banjarmasin) - Fatma Kirana; Ika Kusuma Wardani; Renie Kumala Dewi; Rahmad Arifin; Isnur Hatta (Malahayati Nursing Journal, 2024)
ABSTRACT The definition of dental anxiety is fear of dental procedures. The prevalence of dental anxiety was found to range from 5.7% to 20.2% across all age groups and was closely related to sociodemographic factors such as age, gender, and socioeconomic status. For patients between the ages of 18 and 40, dental anxiety can be the result of traumatic formative experiences involving dental and oral care. To analyze the relationship of sociodemographic factors which include age, gender, and socioeconomic the level of patient anxiety about treatment at the dentist based on early adulthood at RSGM Gusti Hasan Aman Banjarmasin, South Kalimantan. The investigation employed a cross-sectional, analytic observational design. According to the research criteria, the sample size was calculated using the correlative analytic formula, which yielded 85 respondents. This study utilized the Kleinknecht DFS (Dental Fear Survey) to assess the anxiety level of early adult patients in the field of dental care. This questionnaire consists of 20 questions grouped into three dimensions: avoidance of dental appointments, patient's physiological reactions, and stimulation of specific dental anxiety. There is a correlation between sociodemographic factors and dental anxiety at the Gusti Hasan Aman General Hospital in Banjarmasin, as demonstrated by a significance level of 0.05 for the Spearman test.  Sociodemographic factors which include age, gender, and socio-economic relationship with the level of dental care anxiety in early adult patients. Keywords: Dental Anxiety, Sociodemography, Early Adulthood, Gender, Socieconomic